2019
DOI: 10.1002/jat.3839
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine alleviated paraquat‐induced mitochondrial fragmentation and autophagy in primary murine neural progenitor cells

Abstract: The developing brain is uniquely vulnerable to toxic chemical exposures. Studies indicate that neural stem cell (NSC) self‐renewal is susceptible to oxidative stress caused by xenobiotics. However, the impact of antioxidants on NSC self‐renewal and the potential mechanisms remain elusive. In this study, primary murine neural progenitor cells (mNPCs) from the subventricular zone were used as a research model. In addition, paraquat (PQ) was used to elicit oxidative stress and N‐acetylcysteine (NAC) was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
4
7
0
Order By: Relevance
“…Newborn C57BL/6 mice were obtained from the Department of Laboratory Animals of Fudan University, and all experimental procedures were approved by the institutional animal care committee and conducted in accordance with Fudan University ethical guidelines. After hypothermic sacrifice, the SVZ were isolated from newborn C57BL/6J mice as previously described (Xiong et al, 2019). The obtained tissue was incubated in 0.05% trypsin–EDTA (Invitrogen, Carlsbad, CA) at 37°C for 3 min, then centrifuged for 5 min at 1000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Newborn C57BL/6 mice were obtained from the Department of Laboratory Animals of Fudan University, and all experimental procedures were approved by the institutional animal care committee and conducted in accordance with Fudan University ethical guidelines. After hypothermic sacrifice, the SVZ were isolated from newborn C57BL/6J mice as previously described (Xiong et al, 2019). The obtained tissue was incubated in 0.05% trypsin–EDTA (Invitrogen, Carlsbad, CA) at 37°C for 3 min, then centrifuged for 5 min at 1000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the available papers reporting the ability of NAC to modulate the autophagy process are summarized in Table 8 . To start with, NAC supplementation has been found to alleviate paraquat-induced oxidative stress in primary murine neural progenitor cells, resulting in the suppression of autophagy and partial inhibition of Pink1 and Parkin -mediated mitophagy [ 189 ]. Another study reported that NAC attenuated olanzapine-induced overexpression of the LC3-II protein in mHypoA-59 hypothalamic neurons [ 190 ].…”
Section: Modulation Of Autophagy By Nutraceuticals: Support For the T...mentioning
confidence: 99%
“…As differentiation of stem cells involves extensive cellular remodeling, autophagy ensures the elimination of unnecessary cellular components to maintain an optimal cellular status. It was demonstrated that pretreatment of antioxidant N-acetylcysteine (NAC) attenuated oxidative stress-induced NSCs' self-renewal disruption by suppressing autophagy signaling mTOR and decreased LC3B-II protein expression ( 59 ). In contrast, enhancing autophagy in aged satellite cells prevented the senescence and restored regenerative properties ( 60 ).…”
Section: Mitochondrial Function and Hippocampal Plasticity And Neurog...mentioning
confidence: 99%